1998
DOI: 10.1111/j.1438-8677.1998.tb00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Atmospheric NO2 by Spruce (Picea abies) Trees. III. Interaction with Nitrate Reductase Activity in the Needles and Phloem Transport

Abstract: In order to compare the effects of excess pedospheric and atmospheric nitrogen supply on nitrate reductase activity (NR, EC 1.6.6.1) excised spruce branches were exposed to nitrate solutions or were fumigated with N0 2 • Immersion of spruce branches in 6 mM nitrate caused an increase in NR activity by a factor of 14 or 19 in current-year and in one-year-old needles, respectively, as compared to controls incubated in tap water. Exposure to 65 nll-1 N0 2 increased NR activity by a factor of 1.5 in current-year n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
9
0
2
Order By: Relevance
“…Eventually, the atmospheric N influx is metabolized, after passage through the plasmalemma, to ammonium as a result of an enzymatic pathway by nitrate and nitrite reductase in the cytosol and chloroplasts (Beevers & Hagemann, 1983; Wellburn, 1990; Amman et al. , 1995; Weber et al. , 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the atmospheric N influx is metabolized, after passage through the plasmalemma, to ammonium as a result of an enzymatic pathway by nitrate and nitrite reductase in the cytosol and chloroplasts (Beevers & Hagemann, 1983; Wellburn, 1990; Amman et al. , 1995; Weber et al. , 1998).…”
Section: Introductionmentioning
confidence: 99%
“…, 1996); (2) nitrate reductase activity (NRA) (Von Ballmoos et al. , 1993; Weber et al. , 1998) and (3) incorporation of the airborne nitrogen into free amino acids (Nussbaum et al.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake efficiency varies across plants and is influenced by environmental conditions. Studies at leaf level and within leaves have found that after entering the stomata, NO2 is metabolized through dissolution and enzyme-catalyzed reactions (Hu et al, 2014;Nussbaum et al, 1993;Vallano and Sparks, 2008;Weber et al, 1998). Unlike NO2 and O3, foliar exchange of NO is small to insignificant (Hereid and Monson, 70 2001;Rondón et al, 1993), except for herbicide-treated soybeans (Klepper, 1979) and nutrient-fed sugar cane, sunflower, corn, spinach, and tobacco plants (Wildt et al, 1997), where NO emission was observed.…”
mentioning
confidence: 99%
“…Across the stomata, the deposition is a diffusion-controlled process Weber et al, 1998), where the expected rate is the product of the stomatal conductance of water multiplied by the square root of the ratio of the molecular weight of water to the molecular weight of NO2:…”
mentioning
confidence: 99%
“…Виявлено, що індукування НР світлом і нітратами забезпечує адитивні ефекти і стимулюється цитокінінами [11]. Показано, що NO 2 , який є основним компонентом газоподібних викидів автотранспортних засобів, може поглинатися рослинами після окиснення до нітрату і спричинювати підвищення нітратредуктазної активності чи білків НР у мезофілі листків [13][14][15]. Довготривала посуха призводить до інактивації та деградації НР [16], а короткотривалий водний стрес зумовлює зворотну інактивацію НР, що припиняється додаванням НАДН чи фериціаніду [17].…”
unclassified